Karakterisasi Senyawa Bioaktif Dari Kulit Buah Naga (Hylocereus spp). Untuk Aplikasi Masker Rambut - Nurhalizah Tolla Ts, Siti; Sinardi, Sinardi (UIR Press, 2025)
Hair damage is not a trivial problem, because hair health is an important issue for women because it can reduce self-confidence in appearance. The purpose of this study was to determine the composition comparison of dragon fruit skin extract and to determine the feasibility of a hair mask from dragon fruit skin extract to maintain healthy hair and maintain the scalp. The process of making the mask begins by preparing dried dragon fruit skin and extracting it using 70% ethanol as much as 750 mL. The extract results are mixed with the addition of distilled water in various ratios, namely with a volume ratio between dragon fruit skin extract and distilled water of 1: 1, 2: 1, 3: 1, and 4: 1 where 15 mL of dragon fruit skin extract and 15 mL of distilled water, 20 mL of dragon fruit skin extract and 10 mL of distilled water, 22.5 mL of dragon fruit skin extract and 7.5 mL of distilled water, and 24 mL of dragon fruit skin extract and 6 mL of distilled water. Based on the results of the research conducted, dragon fruit skin extract can be formulated as a hair mask preparation, is a homogeneous and stable preparation with an oil-in-water (M/A) emulsion type, has a pH of 6.0, has a viscosity of 2,655 - 4,507 mPa.s, through Cycling Test for 3 cycles there is no change in shape, color and odor so that it is stable for up to 6 days at room temperature, does not cause irritation to hair or scalp, and is suitable for use in the community.